Numerical investigation on the nanofluids heat transfer inside a porous inclined cavity with wavy boundary - Karimi, B.; Pirmohammadi, M.; Salehi-Shabestari, A. (Archives of Mechanics, 2020)
In the present work, a numerical study on the free-convective heat transfer in a porous media cavity with a wavy boundary was carried out. The validation was done by comparing the results with the experimental data. The cavity inclination angle, material of nanofluid, nanoparticles volume fraction, the Rayleigh number, and porosity of the medium are the parameters which are investigated in this study. Results suggested that, due to the thermophysical properties of Cu particles in water, the heat transfer rate was increased for Cu-Water nanofluid in comparison to Al2O3-Water nanofluid, while the heat transfer rate decreased by increasing the volume fraction of nanoparticles. Numerical results showed that the Rayleigh number has significant effect on the heat transfer rate so that increase in the Rayleigh number from 100 to 10 000 increased the averaged Nusselt number between 2 to 3 times. The effect of porosity on heat transfer proved that the convective heat transfer rate increased with increasing the porosity of the porous medium. The effect of inclination angle of cavity on the heat transfer rate suggested that the optimum angle of cavity causing the highest heat transfer rate from wavy wall is 45°.